A Linguistic and Literary Exploration of At-Tafsir al-Bayani: Unpacking Bint al-Shathi’s Hermeneutical Vision - Muis, Muhsin; Syari’ati, Faqih Ali (Dzil Majaz: Journal of Arabic Literature, 2025)
This study aims to examine Bint al-Shathi’s thought and interpretive approach in her reading of the Qur’an. The research is motivated by the limited scholarly attention to her methodological distinctiveness, particularly her integration of linguistic and literary analysis in Qur’anic exegesis. Employing a qualitative approach with a library-based research design, this study collects data by thoroughly reviewing Bint al-Shathi’s works, especially At-Tafsir al-Bayani li al-Qur’an al-Karim, along with supporting literature such as books, journal articles, and other academic publications related to the research focus. Data were analyzed using content analysis to identify key concepts, interpretive patterns, and analytical frameworks used by the author. The findings reveal that Bint al-Shathi’ adopts a distinctive exegetical method that departs significantly from earlier mufassirun. Her interpretation is characterized by a strong emphasis on Arabic linguistic structures and literary aesthetics, resulting in readings that are both lyrical and metaphorical. This linguistic–literary approach allows her to highlight the expressive power, coherence, and rhetorical depth of Qur’anic discourse. The study contributes to Qur’anic studies by offering a deeper understanding of Bint al-Shathi’s intellectual legacy and demonstrating the relevance of her method for contemporary exegetical scholarship, particularly in bridging linguistic analysis and literary appreciation in tafsir